'Introduction to drug disposition and pharmacokinetics' by Stephen H Curry and Robin Whelpton. (21st February 2018) - Hill, Howard M
Stephen H Curry and Robin Whelpton. Introduction to drug disposition and pharmacokinetics. Publisher: Wiley ISBN: 978–1–119–26104–9